STUDIES ON THE CHARACTERISTIC pH OF HAEMOGLOBINS (1972)
The thermodynamics of the azide binding reactions of the hybrids of human and canine haemoglobins (i.e. α2Aβ2Ca and α2Caβ2A) as well as the isolated α and ß polypeptide chains of human and canine haemoglobins have been studied at various pH's and temperatures. Plots of -ΔH° against pH, for all the species, show a distinct maximum. The pH at which the maximum value of - ΔH° occurs is termed the 'characteristic pH' (pH ch). From the results it is concluded that the value of pH ch for the haemoglobin tetramer is an average of the pH ch's of the separate α and ß polypeptide chains although: the form of the curve of -ΔH° against pH is a function of the tetramer and cannot be obtained by averaging -ΔH° values for the individual chains. The Bohr effect of the two hybrids has also been measured and compared with that of the parent haemoglobins. A study of the equilibrium reaction between oxyhaemoglobin and carbonmonoxide was carried out and the accompanying thermodynamic data assessed in terms of the mechanisms postulated for explaining ligand binding reactions of methaemoglobin.